Author Correction: Mechanism and Consequences of The Impaired Hif-1α Response to Hypoxia in Human Proximal Tubular HK-2 Cells Exposed to High Glucose - Coral García-Pastor (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.